Special relations of logical consequence in logics of quasi-ary predicates - Shkilniak, S.S. (PROBLEMS IN PROGRAMMING, 2025)
We introduce and study X–Y-valued relations of logical consequence for first-order composition-nominative logics of partial single-valued, total multiple-valued and partial multiple-valued predicates. A number of properties of the defined relations is obtained, particularly the properties of quantifier elimination. Such properties will be the basis for construction of corresponding sequent calculi.Prombles in programming 2011; 4: 36-48